Convergence without hard criteria: Does EU soft law affect domestic unemployment protection schemes? - Jörg Paetzold; Olaf van Vliet (University of Salzburg, Department of Social Sciences and Economics, 2012)
The European Employment Strategy (EES) aims to promote convergence of domestic labour market policies by soft law instruments. Previous studies on the impact of the EES are mainly focused on active labour market policies. The present study aims at explaining cross national variation in national passive labour market policies and unemployment benefit levels. Building on the most recent measures and pooled time series data, the empirical findings reveal the presence of a convergence process among the most advanced economies regarding passive labour market policy efforts, with the EES fostering this trend even further. Furthermore, our findings support the argument that the EES creates pressure on governments to reform domestic labour market policies, but this pressure varies across countries and over time. The results suggest that the recommendations from the European Council have contributed to unemployment benefit reform processes.
Keywords: H53; J68; 330; Passive labour market policies; convergence; European Employment Strategy; Europeanization; Open Method of Coordination; welfare state